Causes, consequences and treatment of vitamin D deficiency in humans - Marko ,; Kašiković-Lečić, Svetlana (Medicinski časopis, 2024)
This group of vitamins consists of vitamin D2 and vitamin D3, which are synthesized in the body of some invertebrates and plants, but also in the human body. Synthesis of vitamin D takes place in the skin under the influence of ultraviolet rays. The vitamin is transported via specific proteins to all parts of the body, where it performs numerous roles. Vitamin D deficiency is a current public health problem. Vitamin D deficiency is especially pronounced among elderly and  obese. Vitamin D deficiency has a negative effect on the work of the immune system by causing inadequate activation of both innate and acquired immunity, which results in frequent infections. For example, vitamin D deficiency is associated with a more severe clinical picture in persons infected with the SARS-CoV-2 virus. Currently, vitamin D deficiency is associated with an increase in bone and cardiovascular diseases, diabetes, malignant, autoimmune and  allergic. That is why it is extremely important to determine and correct the deficiency of this vitamin in a timely manner. Compensation can be done partly through food, but also through oral supplements, and in more severe cases, by intramuscular administration of vitamins.
Keywords: vitamin D, endocrine system, cardiovascular system, immune system, malignant diseases, bone system.